Developing a Dynamic Conceptual Model of a Home-Based Palliative Care Plan Using the Comprehensive Primary Health Care (PHC) Approach - Kirtania, Mousami; Katta, Ajitha (National Journal of Community Medicine, 2024)
Background: Palliative Care (PC) was a core component of Primary Health Care services during the World Health Assembly Resolution, 2014. The study aims to develop a Comprehensive Palliative Care Model (CPCM) for patients with life-threatening conditions compliant with the local context and unmet needs. Materials and Methods: A mixed-methods approach will be adopted for the three-phased study in two districts of Telangana. Phase I, a literature review, will be performed to explore globally available PC models, followed by an on-ground observational study. Phase II will address the gaps in existing models while identifying the unmet needs of the patients and caregivers. The outcome of the above phases will help develop a CPCM in Phase III. The developed model will be validated using the Delphi technique. Results: The expected outcomes of the study are a) Phase-I: Details of the PC models available globally and locally, b) Phase-II: Availability of essential resources in the Health and Wellness Centers (HWCs), Knowledge and Attitude of the PC team, Barriers to provide PC, Unmet needs, and c) Phase-III: CPCM model Conclusion: The study attempts to provide a holistic PC model, considering the health system, patients, and caregivers and offering policy suggestions to the state.